In vitro evaluation of hydro-ethanolic seed extract of Zanthoxyllum armatum DC to establish its mechanism of action for paralysis of Paramphistomum cervi in continuation with in vivo experimentation in naturally infected goat - Hazarika S.; Barua C. C.; Mohan P.; Das A.; Hazorika M.; Tamuly S.; Pathak P.; Borah B.; Phangchupi D.; Chakraborty A.; George S. (Helminthologia)
The study aims to evaluate the anthelmintic potential of hydro-ethanolic seed extract of Zanthoxyllum armatum (HESEZA) DC against Paramphistomum cervi, a rumen amphistome highly prevalent in North-East India. In vitro and in vivo experiments were carried out to evaluate the anthelmintic property of HESEZA and the mechanism of action against Paramphistomum cervi. In vitro motility and different biochemical estimations like glucose uptake, glycogen content, lactic acid production and acetylcholinesterase (AChE) activity of the extract and standard drug treated worms were studied to explore the mechanism of action. HESEZA @ 3000 μg/ml showed complete death of worms within 1 hr of exposure. Glucose uptake was reduced significantly (P<0.05) by the HESEZA @ 300, 1000 and 3000 μg/ml. Similarly, glycogen content was found to decrease significantly (P<0.05) by the HESEZA @ 300, 1000 and 3000 μg/ml. However, lactic acid production was increased significantly (P<0.05) by the HESEZA @ 300, 1000 and 3000 μg/ml. On the contrary, AChE activity of the P. cervi was reduced significantly (P<0.05) @ 3000 μg/ml by the HESEZA. An in vivo experiment of HESEZA @ 150 and 250 mg/kg body weight in naturally infected goats were accomplished with complete reduction of EPG count on 28th day of post-treatment of the extract @ 250 mg/kg b. wt. All the haematological and biochemical parameters were estimated during in vivo experimentation in goats with HESEZA.